2014
DOI: 10.1016/j.bone.2014.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Circulating interleukin-8 levels explain breast cancer osteolysis in mice and humans

Abstract: Skeletal metastases of breast cancer and subsequent osteolysis connote a dramatic change in the prognosis for the patient and significantly increase the morbidity associated with disease. The cytokine Interleukin 8 (IL-8/CXCL8) is able to directly stimulate osteoclastogenesis and bone resorption in mouse models of breast cancer bone metastasis. In this study, we determined whether circulating levels of IL-8 were associated with increased bone resorption and breast cancer bone metastasis in patients, and invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 44 publications
3
61
0
Order By: Relevance
“…Another study confirmed previous study and reported that IL-8 is associated with stage disease, detected as a prognostic factor (13,14). Kamalakar reported that interleukin-8 plays a main role in osteolysis of patients with breast cancer, and anti-interleukin-8 therapy may be useful in the treatment of skeletal-related events associated with breast cancer (15). However, Zuccari et al reported that the decreased level of IL-8 is associated with local recurrence and/or metastasis in patients with breast cancer (4).…”
Section: Contextsupporting
confidence: 74%
See 1 more Smart Citation
“…Another study confirmed previous study and reported that IL-8 is associated with stage disease, detected as a prognostic factor (13,14). Kamalakar reported that interleukin-8 plays a main role in osteolysis of patients with breast cancer, and anti-interleukin-8 therapy may be useful in the treatment of skeletal-related events associated with breast cancer (15). However, Zuccari et al reported that the decreased level of IL-8 is associated with local recurrence and/or metastasis in patients with breast cancer (4).…”
Section: Contextsupporting
confidence: 74%
“…Furthermore, the existence of ER-α and ER-β in ER negative cancer cells decreased the expression of IL-8 about 40% (23). Kamalkar et al showed that primary human invasive ductal carcinoma may have IL-8 and its expression dose not correlate to Estrogen receptor status (15). Besides, Estrogen activity inhibition with anti-estrogens did not increase the expression of interleukn-8 in breast cancer cells (23).…”
Section: Il-8 and Estrogen Receptorsmentioning
confidence: 99%
“…IL-8 is of particular interest as elevated levels of this chemotactic and inflammatory chemokine have been linked to various aspects of malignancy including increased tumor angiogenesis, invasion, and bone-metastatic capability of breast cancer [21, 22]. For example, the more invasive character of estrogen (ER) negative vs. ER positive breast cancer cells is related to increased levels of IL-8 [23].…”
Section: Introductionmentioning
confidence: 99%
“…IL-8, a prototypical member of a superfamily of small, inducible, secreted CXCs (chemokines) or α-chemokines originally identified as monocyte-derived factors capable of attracting and activating neutrophils, is expressed by a number of cancer cell lines in vitro. Numerous correlations were observed between breast cancer tumor cell IL-8 expression, plasma levels of IL-8, and metastatic potential to bone [54,68,69], also evaluating how chemical and physical properties of specific biomineralized culture platforms can alter breast cancer cell growth and secretion of tumorigenic IL-8 [70]. Increased levels of IL-8 were also highlighted in sera of mice with bone metastases and, together with IL-6, it might be responsible for the attraction of cancer stem-like cells to bone and might support the phenotypic switch [53].…”
Section: Il-8mentioning
confidence: 99%